LA ONDA U II - ZUCKERMANN, R; ESTANDIA CANO, A (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1973)
In the cat, dog, and tortoise the duration of the period of cardiac inhibition obtained by electrical stimulation of the vagus is shortened by an increase in the frequency of stimulation The same frequency repeated in successive periods of activation pr
ARCH INST CARDIOL MEX
Keywords: ONDA; CIENCIAS MEDICAS; MEDICINA INTERNA; CARDIOLOGIA